Soldier Competency Improvement and Development Strategy Indonesian Navy in Manning the New Generation of Defense Equipment - Abdul wahid, Nur Rizal; Siladjaja, Muljanto (Dinasti International Journal of Digital Business Management, 2025)
The Indonesian Navy is a state defense tool that secures the sovereignty of the territorial waters of the Republic of Indonesia, equipped with various types and sizes of warship defense equipment. In supporting its main tasks, KRI is equipped with sophisticated and modern equipment that aims to facilitate monitoring, taking action and implementing war strategies. In the Presidential Decree concerning the Fulfillment of Defense and Security Needs of the Ministry of Defense and the TNI in 2020-2024, so that the fulfillment of defense equipment will begin to be implemented for the next 25 years. To support the government's vision and mission, the Indonesian Navy requires a Human Resource development strategy based on Competency based on qualifications. This is important to implement because HR has a very strong influence and role in the operation and maintenance of KRI. The purpose of this study is to determine the strategies and efforts that have been, will be and need to be carried out by the Indonesian Navy in recruiting, creating and developing professional Indonesian Navy soldiers with qualified competencies according to qualifications. The results of this study are that in the implementation of recruitment, currently there are still problems related to interest and understanding in the world of Education. Basic branch education that has not implemented updated applied technology and its development. In specialization development education, the curriculum tends to be a review of standard equipment installed without conducting a review of new and future technology. In addition, the teaching staff are considered to have not followed the development of the current warship technology situation. In order to fulfill the government's demands in realizing the independence of the Indonesian Navy, a Corporate University strategy is needed which truly plays a role in leading to Collaboration, Change, and Complexity.